The Cambridge companion to new religious movements - Hammer, Olav.; Rothstein, Mikael (Cambridge ; New York : Cambridge University Press, 2012)
"New religions emerge as distinct entities in the religious landscape when innovations are introduced by a charismatic leader or a schismatic group leaves its parent organization. New religious movements (NRMs) often present novel doctrines and advocate unfamiliar modes of behavior, and have therefore often been perceived as controversial. NRMs have, however, in recent years come to be treated in the same way as established religions, that is, as complex cultural phenomena involving myths, rituals and canonical texts. This Companion discusses key features of NRMs from a systematic, comparative perspective, summarizing results of forty years of research. The volume addresses NRMs that have caught media attention, including movements such as Scientology, New Age, the Neopagans, the Sai Baba movement and Jihadist movements active in a post-9/11 context. An essential resource for students of religious studies, the history of religion, sociology, anthropology and the psychology of religion"--
Part I. Social science perspectives. The sociology of new religious movements / David G. Bromley -- New religious movements and the evolving Internet / Douglas E. Cowan -- Major controversies involving new religious movements / James T. Richardson -- Part II. Themes. History and the end of time in new religions / Garry W. Trompf -- Charismatic leaders in new religions / Catherine Wessinger -- Rituals in new religions / Graham Harvey -- Canonical and extracanonical texts in new religions / Olav Hammer and Mikael Rothstein -- Part III. New religious movements. Scientology : up stat, down stat / James R. Lewis -- Neopaganism / Sabina Magliocco -- r Theosophy / James A. Santucci -- The New Age / George D. Chryssides -- "Jihadism" as a new religious movement / Reuven Firestone -- New religious movements in changing Russia / Marat Shterin -- New religious movements in sub-Saharan Africa / Peter B. Clarke.
Includes bibliographical references and index.
Keywords: Cults